(untitled) (Swiss Medical Weekly, 2017)
BACKGROUND Previous cross-sectional studies reported a high prevalence of ascending aorta dilations/aneurysms in male adults with Fabry disease, independently of cardiovascular risk factors. AIMS OF THE STUDY To characterise the remodelling of the ascending aorta in classic Fabry disease under long-term enzyme replacement therapy. METHODS Diameter of the ascending aorta was measured with magnetic resonance imaging at the sino-tubular junction (STJ), and proximal (pAsAo), and distal ascending aorta (dAsAo) at baseline, and after 5 and 10 years of enzyme replacement therapy in 15 adult Fabry patients (10 males; 5 females). RESULTS Over a mean follow-up of 9.5 years, the annual expansion rates measured in 10 males with Fabry disease were 0.41 ± 0.16, 0.36 ± 0.25 and 0.41 ± 0.26 mm/y at the STJ, pAsAo and dAsAo, respectively. Expansion rate at the pAsAo level in male patients was significantly higher than the expected expansion projected from theoretical normal values: 0.36 ± 0.25 vs 0.13 ± 0.05, p = 0.017. In 5 females, the annual expansion rates at the STJ, pAsAo and dAsAo were 0.14 ± 0.11, 0.21 ± 0.18 and 0.26 ± 0.24 mm/y, respectively. There was no significant difference from the projected normal expansion rate at the level of the pAsAo: 0.21 ± 0.18 vs 0.13 ± 0.04, p = 0.39. CONCLUSION Our data suggest that the remodelling of the ascending aorta is more pronounced in male patients with Fabry disease under long-term enzyme replacement therapy compared with the progression observed in a large population study.